Theoretical Development of Urbanization Study in the Third World and It's Relevance on Rural Urbanization Research - M.R. Djarot S. Widyatmoko (Indonesian Journal of Geography, 2008)
At least.. there are /11.'0 points of concern in the urbanization studies, i.e. to see urbanization as a process of structural change of rural population (and areas) and to give attention to the interrelationships (in terms of economic, demographic,political. cultural, technological, social changes) between two different types ofgeographical areas, i.e. urban and rural. These two points of concern lay afoundation for a further development of recent~v urbanization studies, called rural urbanization. So far. it is indicated there are three main streams of perspectives in urbanization studies, i.e. modernization, dependence, and inter-dependence urbanization. Each of these perspectives gives a special color on rural urbanization process. At least there are three fimdamental questions that can be raised from theoretical discussion of urbanization, i.e. (1) are distinct regions that recentlyemerge different from what conventionally known as rural and urban areas; and ifthese are special regions. (2) what are the underlying factors and forces that encourage the emergence of these distinct regions? (3). what kind of policies needed to effectively to cope the development of these distinct regions? These three questions actually are underlying three main areas of rural urbanization researchin a certain region, i.e.: (1) answering WHAT. WHERE, and HOW of the process of rural urbanization; (2) finding the main factors affecting the process; and (3) what kind of actions can be carried out dealing with rural urbanization 'problems